Physical education facilities and equipment of selected secondary schools in Cebu City an evaluation study - Bono, Fe (Violanda) 1928- (s.n.], 1970)
The aim of the study is to evaluate the physical education facilities and equipment in selected secondary schools in Cebu City during the school year 1968-1969. It also assessed the adequacy of such facilities and equipment in relation to the objectives of physical education.